2012
DOI: 10.1007/s00784-012-0713-5
|View full text |Cite
|
Sign up to set email alerts
|

EGCG blocks TGFβ1-induced CCN2 by suppressing JNK and p38 in buccal fibroblasts

Abstract: The exceptional signal transduction pathways of TGFβ1-induced CCN2 production in BMFs contribute to the resistance of PGE(2) downregulation of CCN2 expression; therefore, the CTGF/CCN2 levels are maintained in the OSF tissues in the presence of COX-2. EGCG may serve as a useful agent in controlling OSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 29 publications
4
34
3
Order By: Relevance
“…If the ECM of the tumour could be modified, then drug penetration into the tumour might be facilitated. Table alludes to effects of various treatment modalities on CAFs.…”
Section: Targeting Of Caf‐related Signalling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…If the ECM of the tumour could be modified, then drug penetration into the tumour might be facilitated. Table alludes to effects of various treatment modalities on CAFs.…”
Section: Targeting Of Caf‐related Signalling Pathwaysmentioning
confidence: 99%
“…Curcuminoids (<100 nM) were able to block ECM deposition and TGF‐β/p‐SMAD‐2 signalling pathways in keloid, a fibrotic disease characterised by the abnormal accumulation of ECM in the dermis, with further evidence for anti‐fibrotic effects observed following inhibition of the bleomycin‐induced fibrotic progression in the mouse lung . Another compound with potential anti‐fibrotic activity is the tea polyphenol Epigallocatechin gallate (EGCG), which inhibited TGFβ‐mediated oral submucous fibrosis via suppression of p‐38 mitogen activated protein kinase (p‐38 MAPK) and c‐jun NH2‐terminal kinase (JNK) phosphorylation . Recently, the Src kinase inhibitor Saracatinib (AZD0530) was shown to prevent TGF‐β‐induced Src activation in human lung fibroblasts, preventing transition to a myofibroblast phenotype …”
Section: Targeting Of Caf‐related Signalling Pathwaysmentioning
confidence: 99%
“…76 TGF β is implicated as one of the main triggers for the increased collagen production and decreased matrix degradation pathways in OSF. 52,77 It has been shown that the expression of TGF-β1 was significantly upregulated within the connective tissue of OSF compared to normal mucosa. 62 Treatment of cells with arecanut water extract consisting of polyphenols and alkaloids, has shown that 64% of the differentially regulated genes found in test samples matches with the TGF β induced gene expression profile.…”
Section: Inflammatory Cytokines and Growth Factorsmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG) in turn can completely block TGF β1 induced CCN2 synthesis by suppressing JNK and p38 in buccal mucosal fibroblasts, which may be useful in controlling OSF. 77 Loss of adipose tissue in OSF was found to be due the ability of TGF β to cause lipodystrophy. Level of TGF β secretion is more during the early course of the disease.…”
mentioning
confidence: 99%
“…In an attempt to understand the changes in cytokine levels, gene expression profiling was performed in OSF tissues. The results revealed upregulation of an array of cytokines namely, TGF β 1, TGF β 1p, THBS1, SPP1, TIG1, TGM2 and CTGF and down regulation of BMP7 which is a known negative modulator of fibrosis [24]. TGF β is considered to be a potent stimulator of production and deposition of ECM [25].…”
Section: Growth Factors and Inflammatory Cytokinesmentioning
confidence: 99%